Fungsi dan Peran Pengadilan dalam Pembatalan Sertifikat Overlapping terhadap Permen Agaria/ Kepala BPN No 21 Tahun 2020 Tentang Penanganan dan Penyelesaian Kasus Pertanahan - Yasica Aulia S; Muh Afif Mahfud (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Within the context of implementing Regulation of the Minister of Agrarian Affairs/Head of the National Land Agency (BPN) Number 21 of 2020 concerning the Handling and Resolution of Land Cases, the judiciary holds a central role in the process of annulling overlapping certificates. Overlapping certificates pertain to situations where land ownership conflicts arise due to the overlap of issued certificates. This paper provides an in-depth analysis of the functions and roles of the judiciary in the cancellation of overlapping certificates in relation to the mentioned regulation. The primary function of the judiciary in cases of canceling overlapping certificates based on Regulation of the Minister of Agrarian Affairs/Head of BPN No. 21/2020 is to ensure fair and legally compliant implementation of the regulations pertaining to land case handling. The judiciary possesses the authority to examine and decide the validity of overlapping certificates, taking into consideration legal aspects and evidence presented by the involved parties. In this context, the role of the judiciary also encompasses the interpretation of laws relevant to land ownership dispute resolution. The judiciary also plays a significant role as a mediation avenue to achieve peaceful settlements between the parties involved in overlapping certificate cases. Mediation efforts can help alleviate the judiciary's workload and expedite case resolution. Furthermore, the judiciary holds the responsibility to ensure that land case resolutions adhere to the principles of justice and legal certainty mandated by the regulation. In resolving land cases involving overlapping certificates, the utilization of technology and the expertise of professionals in land surveying and property law also becomes relevant. Geospatial technology and accurate survey evidence can support the judiciary in clarifying land boundaries in question. In conclusion, the judiciary bears a crucial function and role in the process of canceling overlapping certificates pertaining to the implementation of Regulation of the Minister of Agrarian Affairs/Head of BPN No. 21/2020. Through its role in ensuring justice, accurate legal interpretation, and potential mediation, the judiciary can effectively support the handling and resolution of land cases in accordance with the applicable laws and regulations.